Formative evaluation of a community‐based approach to reduce the incidence of Strep A infections and acute rheumatic fever. (24th May 2021) - Wyber, Rosemary; Kelly, Angela; Lee, Anne Marie; Mungatopi, Valerina; Kerrigan, Vicki; Babui, Segora; Black, Nina; Wade, Vicki; Fitzgerald, Christine; Peiris, David; Ralph, Anna P.; ,
Abstract: Objectives : To explore the acceptability of a novel, outreached‐based approach to improve primary and primordial prevention of Strep A skin sores, sore throats and acute rheumatic fever in remote Aboriginal communities. Methods : A comprehensive prevention program delivered by trained Aboriginal Community Workers was evaluated using approximately fortnightly household surveys about health and housing and clinical records. Results : Twenty‐seven primary participants from three remote Aboriginal communities in the Northern Territory consented, providing 37.8 years of retrospective baseline data and 18.5 years of prospective data during the study period. Household members were considered to be secondary participants. Five Aboriginal Community Workers were trained and employed, delivering a range of supports to households affected by acute rheumatic fever including environmental health support and education. Clinical record audit and household self‐report of Strep A infections were compared. No association between clinical‐ and self‐report was identified. Conclusions : Ongoing participation suggests this outreach‐based prevention program was acceptable and associated with improved reporting of household maintenance issues and awareness of prevention opportunities for Strep A infections. Implications for public health : Biomedical, clinic‐based approaches to the management of Strep A infections in remote communities can be usefully augmented by outreach‐based supports delivered by Aboriginal Community Workers responding to community needs.